Comparison of Islamic and General Universities From the Point of View of Student Competence in the Field of Sharia Accounting and Algebra as Measured by Human Resources in the City of Medan - Lubis, Arnida Wahyuni (ITB AAS INDONESIA Surakarta, 2024)
The aim of the research is to determine the level of competency required in terms of knowledge of sharia accounting and algebra, to maintain stakeholder trust. To determine the level of human resource development which is a milestone for overcoming future challenges to improve quality or quality graduates. This research uses a descriptive statistical research approach. Where the definition of a descriptive statistical research approach is a type of research whose aim is to present a complete picture of a social setting or is intended for exploration and clarification of a phenomenon or social reality, by describing a number of variables relating to the problem and unit being studied among the phenomena being tested. . method by collecting secondary data, namely articles, research results and reference books published over the last 5 years. It will be described using analysis and using statistical data testing methods. Based on the description above, the author finds that the level of student competency in the fields of sharia accounting and algebra as measured by human resources in the city of Medan is quite good, with the following details: Students with a level competence is measured by human resources in the field of sharia accounting as much as 8.46%. Students who are not competent and not supported by human resources in the field of sharia accounting are 1.49%. Students whose level of competence is measured by human resources in the field of science algebra as much as 8.0%, students who are not competent and not supported with human resources in the field of algebra as much as 2.0%. The condition of being incompetent and not supported by human resources is influenced by: learning processes and career development that are not yet fully optimal Keywords: Competency, Human Resources, Students, Sharia Accounting Science, Algebra Science